Approaching Superior Potassium Storage of Carbonaceous Anode Through a Combined Strategy of Carbon Hybridization and Sulfur Doping. Issue 3 (26th August 2021) - Yao, Qianqian; Gan, Yanmei; Ma, Zuju; Qian, Xiangying; Cai, Suzhi; Zhao, Yi; Guan, Lunhui; Huang, Wei
Abstract : Carbonaceous materials are promising anode candidates for potassium‐ion batteries (PIBs) given its high conductivity, stable property, and abundant resource, while its practical implementation is still hampered by its limited capacity and inferior rate behavior. Herein, we report a superior carbonaceous anode through a combined strategy of carbon hybridization and heteroatom doping. In this composite, hollow carbon spindles (HCS) were anchored on the surface of graphene (G) followed with sulfur doping treatment, aiming to integrate the high conductivity of graphene, the good structure stability of HCS, and the S doping‐induced ample active sites. As a PIB anode, the S‐G@HCS composite can display high capacity (301 mA h g −1 at 0.1 A g −1 after 500 cycles) and long‐term cyclability up to 1800 cycles at 2 A g −1 . Impressively, it can deliver an outstanding rate capacity of 215 mA h g −1 at 10 A g −1, which is superior to most carbon anodes as‐reported so far for PIBs. Experimental and theoretical analysis manifests that the construction of graphene/amorphous carbon interface as well as S doping enables the regulation of electronic structure and ion adsorption/transportation properties of carbonaceous material, thus accounting for the high capacity and superior rate capability of S‐G@HCS composite. Abstract : A combined carbon hybridization and sulfur doping strategy is developed for boosting the performance of carbonaceous materials. Benefiting from the synergistic effect of graphene/amorphous carbon heterointerface and S doping on the enhancement of electrical conductivity and ion transport/adsorption ability, as‐prepared S‐G@HCS exhibits high capacity and excellent rate performance (215 mA h g −1 at 10 A g −1 ), outperforming most reported carbon anodes.